Targeting tumor cells with pyrazolo[3,4-d]pyrimidine scaffold: A literature review on synthetic approaches, structure activity relationship, structural and target-based mechanisms - Mohamed A. Abdelgawad; Nadia A.A. Elkanzi; A.A. Nayl; Arafa Musa; Nasser Hadal Alotaibi; W.A.A. Arafa; Sobhi M. Gomha; Rania B. Bakr (Arabian Journal of Chemistry, 2022)
Pyrazolo[3,4-d]pyrimidine had been attracted awesome interest due to its pharmacological potential especially as an anticancer. Several mechanisms of action were accounted for the anticancer potential of this privileged scaffold. Previous researches explained its role in binding with many receptors as cyclin-dependent kinases, epidermal growth factor receptor, Src kinase, m-TOR, and JAK kinase. Nevertheless, there is an incredible demand for the discovery of target-oriented compounds. In this review, we shed the light on the antitumor potential of this important fused heterocyclic system, different mechanisms of actions of this ring, and SAR studies towards many targets in a trial to pave the way for medicinal chemists to optimize this ring system in order to discover new anticancer agents with better selectivity and increased anticancer potential.